2012
DOI: 10.1095/biolreprod.111.095760
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Distinct Populations of Prostasomes That Differentially Express Prostate Stem Cell Antigen, Annexin A1, and GLIPR2 in Humans1

Abstract: In addition to sperm cells, seminal fluid contains various small membranous vesicles. These include prostasomes, membrane vesicles secreted by prostate epithelial cells. Prostasomes have been proposed to perform a variety of functions, including modulation of (immune) cell activity within the female reproductive tract and stimulation of sperm motility and capacitation. How prostasomes mediate such diverse functions, however, remains unclear. In many studies, vesicles from the seminal plasma have been categoriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
146
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 201 publications
(167 citation statements)
references
References 59 publications
18
146
1
2
Order By: Relevance
“…Furthermore, in vivo, local administration of synthetic NPs containing Ac2-26 mimics the prorepair effects of epithelial and immune cell-derived EVs. Additionally, a previous study reported ANXA1 association with the exoplasmic surface of vesicles secreted by prostate epithelial cells into the seminal fluid or prostasomes may contribute to suppression of the immune response in the female reproductive tract (39).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in vivo, local administration of synthetic NPs containing Ac2-26 mimics the prorepair effects of epithelial and immune cell-derived EVs. Additionally, a previous study reported ANXA1 association with the exoplasmic surface of vesicles secreted by prostate epithelial cells into the seminal fluid or prostasomes may contribute to suppression of the immune response in the female reproductive tract (39).…”
Section: Discussionmentioning
confidence: 99%
“…2A). Overlaying the gradient on top of the EV pellet ensured that membrane-enclosed vesicles floated upwards, whereas protein aggregates could not float into the gradient and remained in the dense fractions (14,15). Ten fractions were recovered and analyzed for the presence of protein markers previously detected in both pellets.…”
Section: Floatation Into Iodixanol or Sucrose Gradients Differently Smentioning
confidence: 99%
“…In subsequent years, many additional cell types of both hematopoietic and nonhematopoietic origin, such as cytotoxic T cells, platelets, mast cells, neurons, oligodendrocytes, Schwann cells, and intestinal epithelial cells, have been shown to release exosomes (Simons and Raposo 2009;Théry et al 2009). Furthermore, exosomes have been found in many body fluids, including blood (Caby et al 2005), semen (Aalberts et al 2012), urine (Pisitkun et al 2004), saliva (Ogawa et al 2011), breast milk (Admyre et al 2007), ascites fluid (Andre et al 2002), amniotic fluid (Asea et al 2008), cerebrospinal fluid (Vella et al 2007), and bile (Masyuk et al 2010). …”
Section: The Properties Of Exosomesmentioning
confidence: 99%